2009
DOI: 10.1021/jf901074b
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Commercial Wild Rice and Identification of Flavonoid Compounds in Active Fractions

Abstract: The health benefits of whole grain consumption have been attributed to their content of complex carbohydrates, vitamins, minerals, and other phytochemical constituents. Wild rice is a whole grain finding applications in gourmet foods due to its nutritional value and unique taste. However, little is known about its antioxidant properties and phytochemical components. The objectives of this study were to evaluate the antioxidant properties of wild rice. Eleven commercial wild rice samples (raw, mixed, and proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 29 publications
(42 reference statements)
3
87
0
2
Order By: Relevance
“…B-type proanthocyanidin is very common in nature. In red rice, the block unit of proanthocyanidin consists of catechin and epicatechin (Gunaratne et al, 2013;Qiu, Liu, & Beta, 2009), and exists in B-type (Fig. 1c).…”
Section: Chemistry and Bioactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…B-type proanthocyanidin is very common in nature. In red rice, the block unit of proanthocyanidin consists of catechin and epicatechin (Gunaratne et al, 2013;Qiu, Liu, & Beta, 2009), and exists in B-type (Fig. 1c).…”
Section: Chemistry and Bioactivitymentioning
confidence: 99%
“…From pH 3 to 6, anthocyanins change into colorless carbinol pseudobase or chalcone, while in neutral and slightly acidic pH, they turn into neutral quinonoidal bases showing purple to violet color (He & Giusti, 2010). For proanthocyanidins, organic solvent has been used as extractant, such as 80% methanol, acetic acid acidified acetone (Gunaratne et al, 2013;Min et al, 2012;Qiu et al, 2009).…”
Section: Extraction Diversity and Distribution Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengukuran kadar total fenolik kedua beras analog disajikan pada Tabel 1. Total phenolics beras analog A (0,10 ± 0,00 mg GAE/g sampel) dan beras analog B (0,16 ± 0,00 mg GAE/g sampel), sudah lebih tinggi dibandingkan dengan total fenol beras putih yaitu 0,044 mg GAE/g sampel (Qiu, 2009). Hal ini dapat disebabkan oleh penggunaan bahan baku jagung dan sorgum yang mengandung kadar fenolik cukup tinggi yaitu 2,607-3,201 mg GAE/g sampel (De la Parra dkk., 2007) dan 1,44 mg/GAE/g (Moraes dkk., 2015), masing-masing.…”
Section: Hasil Dan Pembahasan Kadar Total Fenolik Dan Serat Pangan Beunclassified
“…It has been demonstrated that apigenin is the main active ingredient in the flower of Chrysanthemum morifolium extract, a widely used traditional Chinese medicine component [6]. Apigenin, in particular, has been highlighted in the recent researches, because of their potential role as the contributing factors to the antioxidant activity, anticarcinogenic activity, hypertension prevention substance and antibacterial qualities [7,8,9]. And apigenin worked fairly well to calm the agitated.…”
Section: Introductionmentioning
confidence: 99%